RESEARCH OF THE PROBLEM OF PERSONAL SELF-CONCEPTION FROM THE VIEWPOINTS OF EASTERN THINKERS - D. E. Yulchiboeva (Galaxy International Interdisciplinary Research Journal, 2023)
The article focuses on the development of self-awareness in the perspective of Eastern thinkers. In it, the main focus is on the fact that the formation of self-awareness in a person is the result of the conditions of the social environment and education, which is reflected in the ideas put forward by them. In particular, they show that the maturity of a person is determined by the level of his perfection.